The Orontes Valley in texts from Alalaḫ and Ugarit during the late Bronze Age, ca 1500-1200 bc - Soldt, Wilfred Hugo van (Le fleuve rebelle, 2016)
The data available in the Late Bronze Age texts from Ugarit and Alalaḫ are not very helpful with regard to the river Orontes, because they do not mention its name and they give no specific information on whether it was navigable or not. Especially in the case of Alalaḫ this is surprising. However, the archives of both cities have provided us with data that help us to reconstruct the borders of these two city-states and in this the Orontes played an important role. Treaties between the Hittite kings and their vassals at Ugarit ensured that the border with Alalaḫ was carefully delineated by listing all toponyms belonging to Ugarit to the south of the border, including those that come close to the river. In administrative texts from Alalaḫ, the city-state was divided in several provinces, one of which seemed to have included a large part of the Ghab.